Variable Presentations in Pulmonary Arteriovenous Malformation - Nasir Ahmad Lone; Akshit Kumar; Waseem Ahmed Sheikh (Asian Journal of Medical Radiological Research, 2020)
Pulmonary arteriovenous malformations (PAVM) are a group of vascular anomalies of lung which present with variable clinical symptoms. Most patients with PAVM are asymptomatic but it can cause dyspnea on exertion, paradoxical emboli to brain causing various central nervous system complications like stroke and brain abscess, hemoptysis and rupture. The age at the presentation can range from 1st to 7th decade but the majority of patients present before the age of 30 years. PAVM is strongly associated with hereditary haemorrhagic telangiectasis which presents with epistaxis, mucocutaneous telangiectasias and AV malformations of various organs. In our case series, we have patients ranging from 3 yrs to 75 years with presentation ranging from asymptomatic to exertional dyspnea, hemoptysis and neurological complications.